Оцінка ефективності грошово-кредитної політики в умовах зростаючої монетизації - Прадун, В.П. (Культура народов Причерноморья, 2006)
In the article is lighted the problem of estimation of efficiency of monetary policy in the conditions of growing counting. Factors which regulate suggestion of money are explored. The analysis of indexes of money - credit market development is conducted. The stages of expansion of demand are considered on a money.